Natural infection of malignant catarrhal fever in Bali cattle: A case study - R Damayanti; A Wiyono (Indonesian Center for Animal Research and Development (ICARD), 2005)
Malignant catarrhal fever in Indonesia is caused by Ovine herpes virus 2 and considered as a disease with high mortality rate causing degeneratif and lymphoproliferative disease in cattle, buffalo and other ruminants. A total number of fifteen Bali cattle were naturally infected by Malignant Catarrhal Fever (MCF). Those cattle were meant to be experimental animals of research on infectious bovine rhinotracheitis (IBR), Septicaemia epizootica (SE), and bovine brucellosis. The clinical signs of those animals were sudden high fever, depression, anorexia, corneal opacity, mucopurulent oculo-nasal discharges and diarrhoea. Six of them were dead and the remaining cattle were slaughtered at extremis. On the basis of clinical, gross-pathological and histopathological findings, all cases were shown to be consistent and pathognomonic of MCF cases. These cases were regarded as an outbreak of MCF affecting Bali cattle which occurred during wet season and while in other paddock in that area there were a number of lambing sheep. This result confirms that Bali cattle is a very susceptible animal of MCF and the cases were very likely due to the spread of MCF virus from lambing sheep. Key Words: Malignant Catarrhal Fever, Bali Cattle, Natural Infection, Pathology